ANALISIS KUALITAS LAYANAN INTERNET KAMPUS MENGGUNAKAN METODE HTB (HIERARCHICAL TOKEN BUCKET) - A.R. Walad Mahfuzhi; Bambang Soedijono; Eko Pramono (Universitas Janabadra, 2017)
Quality of Service (QoS) is not a limit but rather to the quality of the resulting internet services against a method that is used. To generate the required QoS bandwidth management method of a. Hierarchical token bucket (HTB) is a good method to do bandwidth management. The purpose of this study is to conduct an analysis of QoS method using HTB against parameters, delay, throughput and packet loss on the internet service at the Muhammadiyah University of Bengkulu. Testing was done using the mikrotik RB433AH oprasi system that is running on windows 7, as well as the tools used is a command prompt (CMD) and wireshark to do capture data analysis. The resulting QoS by using the method of HTB is 3 and has nice categories based on average index parameters. On testing the parameters of the resulting value is the throughput of 52.17% with index 3. While the resulting value of the delay parameter of 45ms with index 4 and packet loss parameters on testing the resulting value of 18.52% with a value of index 2.Keywords: Quality of Service, HTB, Bandwidth Management, Throughput, Delay, Packet Loss.